The Crimes of Defamation through Social Media in the Saudi Legal System: Cybercrime - Abdulrahman Jameel Ali (International Journal of Law Research and Studies, 2025)
Islamic law has worked to build a virtuous society in which human beings are honored and protected from anything that diminishes their freedom, dignity, and reputation. Islamic law urges society to protect the rights of individuals and groups, to be free and dignified, to exercise their legitimate rights with complete freedom, and to enjoy all means of comfort without infringing upon the freedom and reputation of others. Islamic law protects the privacy of individuals and groups, and through its tolerant teachings, it preserves human privacy and safeguards their reputation and dignity, both in life and in death. With the recent increase in violations of the sanctity of private life on social media, Islamic law and applicable regulations have taken the lead in criminalizing this practice, as texts from the Holy Quran, the Sunnah, and regulations protect these rights. Websites and social media are electronic networks that aim to achieve social communication between people around the world. Social media has greatly facilitated the commission of many cybercrimes, sounding the alarm not only on the personal or local level, but also on all countries, alerting them to the dangers they pose. Therefore, the researcher divided this chapter into three sections from which several demands and branches emerge. In them, the researcher answers the research questions that include the nature and concept of cybercrimes, their characteristics and types, as well as the means of proof, types and forms of electronic evidence, and finally, the national and international efforts to combat cybercrimes.